Optimization of a CFD – Heap leach model and sensitivity analysis of process operation - Nick Croft (Minerals Engineering, 2013)
A comprehensive heap leach model, developed within a computational fluid dynamics software framework, provides a modeling tool to capture reactive dissolution in low grade ores of oxide and sulfide minerals. These systems involve suites of very complex reactions, which are closely coupled with thermal conditions and key microbial populations. One of the key challenges when modeling heap leach scenarios is characterization of the ores and parameterization of the model in order to utilize the model as an investigative tool. The calibration of the model can be a lengthy process requiring many simulation runs. An optimization tool has been incorporated into the model to allow automated searching for multiple ‘best fit’ parameter values and to determine sensitivity. Once the model has been parameterized, large-scale forecasts can be simulated or a sensitivity analysis can be performed to investigate a range of process variables, such as irrigation rate, lift, air injection, acidity, head grade and dripper emitter spacing, amongst others. One such example is explored here for the Zaldivar ore body.